Tata Laksana Apendisitis Akut di Era Pandemi Covid-19 - Yohni Wahyu Finansah; Aldo Dwi Prastya; Siska Mawaddatunnadila (Universitas Muhammadiyah Surabaya, 2020)
AbstractAppendicitis is an inflammation of the appendix vermiformis caused by a blockage in the formof fecalit or infection and is the cause of most cases of acute abdomen that occur. Acuteabdomen requires emergency action, many cases of appendicitis in Indonesia require fast andprecise action to prevent perforation. The diagnosis of acute appendicitis is based on history,physical examination, and supporting examinations such as ultrasound examination (USG).Management of appendicitis can be operative and non-operative. Conservative managementof antibiotics in uncomplicated appendicitis will have a risk of recurrent appendicitis rangingfrom 16-40% of initial treatment within one year. However, if the patient's condition worsensor treatment with antibiotics is unsuccessful, an appendectomy is performed either by opensurgery or by laparoscopy. Acute abdominal pain in Covid-19 patients poses a dilemma fordoctors, delaying surgical management can lead to serious complications and even death. Viceversa, performing unnecessary surgery on Covid-19 patients causes iatrogenic morbidity anddeath. Therefore, the surgeon is obliged to adhere to the protocol established by the IndonesianGeneral Surgeons Society.Keywords: appendicitis, pandemi, COVID-19